" Análisis crítico-jurídico sobre los derechos de las mujeres en período de maternidad en Ecuador." - Valarezo Palacios, Tannia Yaqueline (2025)
A critical-legal analysis was carried out on the rights of women during maternity period in Ecuador, with emphasis on Judgment 878-20-JP/24 of the Constitutional Court. The study was contextualized in the historical and regulatory evolution of women's rights, considering principles of legal equality and specific protection during pregnancy, childbirth and postpartum. The main objective was to identify the interpretative parameters used in judicial processes to guarantee the restoration of these rights. Through a mixed approach, qualitative and quantitative methods were combined, using the interview as the main technique. The results showed a persistent violation of rights, particularly in the areas of work and health, evidencing so inconsistencies in the application of laws and public policies. Judgment 878-20-JP/24 highlighted the failure to provide fundamental guarantees to a judge whose right to maternity leave was suspended following the death of her son, pointing out the need for a comprehensive approach to the protection of these rights. It was concluded that, despite legal progress, effective implementation of regulations remains insufficient, which underlines the importance of strengthening legal training and social awareness to prevent future violations. This analysis seeks to contribute to the formulation of more robust and fair policies to protect women's rights in Ecuador.